(3QSGdI aj GdehGSYI hGdeVGjbIs - (3GdORahdj, GdcGXej, GdCfUGQj, GdJSJQj, MSf Hf CSO Gddg Hf ESeGYjd, J (B1298(3g`s ((3eMeO LhGO Hf eMeO LYaQ GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg Gdj hSYJ QMeJg hYeJ(B... (3hHYO ajbhd (B... (3CSO Gddg Hf ESeGYjd (B... (3gPG jG ENhGfj eG JhGaQJ OhGYjce Ydjg hJXGgQJ eSGYjce Edjgs
(3BNQgG (B:s
(3GdeMGaXI Ydi hbJ GdaVjdI a(B'(3fgG ef CYXe GdSff GdCcjOI(B... (3adfbWY gfG GdcdGe MGeOG ddg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B184s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B539s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs